SEED YIELD AND ITS COMPONENTS OF ALFALFA AS INFLUENCED BY SULFUR AND LAST CUTTING DATE - & et al., Khrbeet (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
A field study was conducted at the experimental farm, Coll. of Agric., Abu-Ghraib, Baghdad, Iraq during the period from mid of march 2013 to end of August 2014 to investigate the effect of different levels of sulfur (0, 1, 2 and 3 ton. ha-1) and three dates of last cutting (1, 10th and 20th,May 2014)_ on seed yield and it’s components of alfalfa local cultivar, Layout of the experiment was R.C.B.D. arranged in split –plots with three replications. Sulfur levels were used as main plot and the time when last cutting occurs was sub-plot. Results, showed that addition of sulfur at level more than 1 ton.ha-1 (2, 3 ton ha-1) resulted in a significant increasment in the No. of seeds per pod, No. of pods per raceme, No. of racemes per stem, No. of stems per m-2 and seed yield kg.ha-1. While, No. of ovules per floret, % of ovules abortion and 1000 seed weight were not significantly influenced by sulfur levels. Highest seed yield (579.4 Kg ha-1) was obtained when sulfur added at level 2 ton ha-1. Plants, when last cutting occurred on 10th of May produced highest No. of pods per raceme, No. of stems per m-2 and seed yield (530.8 Kg h-1). There were no significant effect of last cutting date on, No. of ovules per floret, No. of seed per pod, % of abortion and 1000 seed weight. There were high positive correlation between seed yield and each of No. of seeds per pods, No. of pods per raceme and No. racemes per stem (+0.880, +0.918 and +0.920) respectively. This result suggests that yield components may be good selection criteria for breeding seed yield of alfalfa cultivars. High seed yield can be obtained from stands received 2 ton ha-1 and last cutting occurred on 10th May.